2014 IEEE International Conference on MOOC, Innovation and Technology in Education (MITE) 2014
DOI: 10.1109/mite.2014.7020261
|View full text |Cite
|
Sign up to set email alerts
|

Role of accreditation in engineering education

Abstract: Accreditation can be referred to as the procedure followed for official recognition or quality assurance. It provides the opportunity of promoting excellence in the field of education. It can be stated as the process in which the quality of an educational institution or a particular educational programme is evaluated so as to formally recognize it if it meets certain standards. As per the exponential growth in the number of engineering colleges in India, the process of accreditation is becoming a necessity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…which means that the GAD of sub-objective 1 is 0.812, the GAD of sub-objective 2 is 0.781, and the GAD of sub-objective 3 is 0.763. Based on the value of C i obtained above and the weight of W i (W 1 = 0.5, W 2 = 0.3, and W 3 = 0.2), C is calculated as follows: (5) which means that the GAD of the online cognitive internship course is 0.793.…”
Section: Results Based On Gadmentioning
confidence: 99%
See 1 more Smart Citation
“…which means that the GAD of sub-objective 1 is 0.812, the GAD of sub-objective 2 is 0.781, and the GAD of sub-objective 3 is 0.763. Based on the value of C i obtained above and the weight of W i (W 1 = 0.5, W 2 = 0.3, and W 3 = 0.2), C is calculated as follows: (5) which means that the GAD of the online cognitive internship course is 0.793.…”
Section: Results Based On Gadmentioning
confidence: 99%
“…The EEA (Engineering Education Accreditation), as a quality assurance mechanism for engineering specialties in colleges and universities, is implemented by the professional institutions and based on certain standards [1,2]. It has been reported that its application brings great benefits for colleges and universities to cultivate undergraduate students [3][4][5][6]. At present, there are mainly four types of EEA used worldwide, including the Washington Accord, the Sydney Accord, the Dublin Accord, and the EUR-ACE [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the popular EEA types mainly include the Washington Accord, the Sydney Accord, the Dublin Accord and the EUR-ACE (Patil and Codner, 2007;Turhan et al, 2015). These EEA types can improve the engineering education quality and promote the mutual recognition of engineer qualification in different countries (Harrison and Bond, 2012;Kohli, 2014;He, 2016).…”
Section: Information Modeling and System Realization 921mentioning
confidence: 99%
“…Literature [4] points out that the so-called accreditation is the evaluation procedure to confirm whether an education organization's educational practice can guarantee the achievement of its educational goals according to some widely accepted standards and processes. Compared with traditional education quality evaluation methods, accreditation can not only accurately evaluate the education quality of an education organization, but also promote the education reform and improve the education quality.…”
Section: The Strengths Of the Education Quality Evaluationmentioning
confidence: 99%